Experimental study on the dynamic characteristics of coarse-grained saline soil embankments in the high-cold saline lake area under freeze-thaw cycle action - Dongqing Wang; Xiaohua Yang; Qi Wan; Shasha Zhang (Case Studies in Construction Materials)
To study the dynamic behavior of chloride saline soil embankments in the high-cold saline lake region under traffic loads and freeze-thaw cycles, this paper focuses on the Sebei Qarhan Highway. The indoor dynamic load freeze-thaw cycle model test system was designed and large-scale model tests were conducted based on on-site geological conditions. The study examined the main effects of traffic load amplitude and frequency, embankment fill water content, and freeze-thaw cycles on dynamic stress, strain, and modulus of the embankment. Results showed an approximate linear correlation between load amplitude and dynamic stress, while dynamic stress and strain decreased nonlinearly with depth. Increased load amplitude significantly reduced the dynamic modulus within the 0–0.8 m depth range. Load frequency had minor effects on embankment dynamics. Higher load amplitudes had a greater impact on water content's influence on embankment dynamics. With increased water content, dynamic stress increased while dynamic modulus decreased more significantly within the 0–0.8 m range. Freeze-thaw cycles caused U-shaped variation in soil temperature within the 0.05–0.7 m depth range, with water and salt moving upward. Dynamic strain increased by 30 %-50 % and 70 %-120 % before and after freeze-thaw cycles at 20kPa and 40kPa load amplitudes respectively, with the dynamic modulus of the embankment top from 0 to 0.1 m decreasing by 20.1 % and 33.2 % respectively.